Employee incentives: bonuses or penalties? - Nosenzo, Daniele (IZA, 2016)
Firms regularly use incentives to motivate their employees to be more productive. However, often little attention is paid to the language used in employment contracts to describe these incentives. It may be more effective to present incentives as entitlements that can be lost by failing to reach a performance target, rather than as additional rewards that can be gained by reaching that target. However, emphasizing the potential losses incurred as a result of failure may entail hidden costs for the employer, as it may damage the trust relationship between a firm and its employees.